The Metallicity of the Sun Reviewed from Pre-Main Sequence Evolution - Putri Indriani; Aprilia Aprilia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
Metallicity is defined as the fraction of the abundance of elements heavier than hydrogen and helium. Metallicity has different values for different stellar objects and its value will also change as the star evolves. This research is focused on calculating and analyzing the early metallicity of the Sun, that is at the beginning of the Sun's evolution at the Pre-Main Sequence. Five metallicity samples with an initial mass of 1 M⊙ were used. This study uses the evolution code MESA r-15140 which produces a Hertzsprung-Russell diagram with various metallicities. From the simulation, it is found that the most suitable metallicity is 0.065. There are four dominant elements at the core of the Sun, namely hydrogen, helium, carbon, and oxygen. The density, pressure, and temperature values at the core of the Sun also increase with age.